2020
DOI: 10.2196/24584
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and acceptance of technology-based psychological interventions for the acute treatment of unipolar depression: a systematic review and meta-analysis (Preprint)

Abstract: Background Evidence on technology-based psychological interventions (TBIs) for the acute treatment of depression is rapidly growing. Despite extensive research in this field, there is a lack of research determining effectiveness and acceptance of TBIs considering different application formats in people with a formally diagnosed depressive disorder. Objective The goal of the review was to investigate the effectiveness and acceptance of TBIs in people with diagnosed depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…It is well established that an array of factors need to align in order for a digital innovation to be adopted structurally [ 2 , 10 ], even more so in health care, which is characteristically one of the slowest domains in which to adopt digital innovations [ 59 ]. The beneficial effects of digital health slowly become more apparent, and our findings indicate that the general population also seeks out digital health care if traditional care is disrupted [ 2 , 11 , 60 ]. However, our findings indicate that digital health care–seeking behavior is not sustainable at the current stage of progress, seeing how the search volumes under study frequently reverted to prepandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that an array of factors need to align in order for a digital innovation to be adopted structurally [ 2 , 10 ], even more so in health care, which is characteristically one of the slowest domains in which to adopt digital innovations [ 59 ]. The beneficial effects of digital health slowly become more apparent, and our findings indicate that the general population also seeks out digital health care if traditional care is disrupted [ 2 , 11 , 60 ]. However, our findings indicate that digital health care–seeking behavior is not sustainable at the current stage of progress, seeing how the search volumes under study frequently reverted to prepandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis found that electronically delivered therapist-supported cognitive behavioural therapy (eCBT) was more effective than face-to-face cognitive behavioural therapy (ftfCBT) in reducing depression symptom severity, with a very large standardized mean difference (SMD) of 1.73. 1 Considering that SMDs above 0.80 are usually considered large, 2 that a meta-analytic comparison of CBT with passive controls resulted in SMDs around 0.50 to 0.70, 3 and that other studies reported differing results, 4 , 5 we were surprised to see such an extreme effect. Our concerns were strengthened further by an addendum stating that the direction of the effect was misinterpreted in the original publication.…”
mentioning
confidence: 88%
“…We recommend that criteria for the development of a WBI for ICSOC should be based on different sources. In general psychiatry, where WBIs have shown to be effective in reducing symptoms of disorders (Etzelmüller et al, 2020; Köhnen et al, 2021; Reins et al, 2021), key factors for the effectiveness of WBI could be identified (Knaevelsrud et al, 2016). This enables the identification of criteria that are relevant for the effectiveness of a WBI for ICSOC.…”
Section: Development Of Wbis For Icsocmentioning
confidence: 99%
“…Along with the increasing digitalization of everyday life, information and communication technologies regarding mental health (eMental Health, eMH) have experienced an upswing (Andersson et al, 2019). At present, there are multiple eMH applications for various mental health concerns available (Andersson et al, 2019), and the effectiveness of many applications has been supported in randomized controlled trials (RCT; Etzelmüller et al, 2020; Köhnen et al, 2021; Reins et al, 2021). Based on these studies in the field of general psychotherapy and counseling, eMH has been developed for forensic psychiatry and psychotherapy since the beginning of the 21st century (Kip et al, 2018).…”
mentioning
confidence: 99%